![image](https://tex.z-dn.net/?f=1%29OD3%3A%5C%5C5x-1%3E0%5C%5Cx%3E0%2C2%5C%5Clog_3%285x-1%29%3D2%5C%5C5x-1%3D9%5C%5C5x%3D10%5C%5Cx%3D2%5C%5C%5C%5C3%29OD3%3A%5C%5C2x-3%3E0%5C%5Cx%3E1%2C5%5C%5Clog_4%282x-3%29%3D1%5C%5C2x-3%3D4%5C%5C2x%3D7%5C%5Cx%3D3%2C5)
0\\x>0,2\\log_3(5x-1)=2\\5x-1=9\\5x=10\\x=2\\\\3)OD3:\\2x-3>0\\x>1,5\\log_4(2x-3)=1\\2x-3=4\\2x=7\\x=3,5" alt="1)OD3:\\5x-1>0\\x>0,2\\log_3(5x-1)=2\\5x-1=9\\5x=10\\x=2\\\\3)OD3:\\2x-3>0\\x>1,5\\log_4(2x-3)=1\\2x-3=4\\2x=7\\x=3,5" align="absmiddle" class="latex-formula">
![image](https://tex.z-dn.net/?f=5%29OD3%3A%5C%5C3x-1%3E0%5C%5Cx%3E%5Cfrac%7B1%7D%7B3%7D%5C%5Clg%283x-1%29%3D0%5C%5C3x-1%3D1%5C%5Cx%3D%5Cfrac%7B2%7D%7B3%7D%5C%5C%5C%5C2%29OD3%3A%5C%5C3x%2B1%3E0%5C%5Cx%3E-%5Cfrac%7B1%7D%7B3%7D%5C%5Clog_5%283x%2B1%29%3D2%5C%5C3x%2B1%3D25%5C%5Cx%3D8)
0\\x>\frac{1}{3}\\lg(3x-1)=0\\3x-1=1\\x=\frac{2}{3}\\\\2)OD3:\\3x+1>0\\x>-\frac{1}{3}\\log_5(3x+1)=2\\3x+1=25\\x=8" alt="5)OD3:\\3x-1>0\\x>\frac{1}{3}\\lg(3x-1)=0\\3x-1=1\\x=\frac{2}{3}\\\\2)OD3:\\3x+1>0\\x>-\frac{1}{3}\\log_5(3x+1)=2\\3x+1=25\\x=8" align="absmiddle" class="latex-formula">
![image](https://tex.z-dn.net/?f=4%29OD3%3A%5C%5Cx%2B3%3E0%5C%5Cx%3E-3%5C%5Clog_7%28x%2B3%29%3D2%5C%5Cx%2B3%3D49%5C%5Cx%3D46%5C%5C%5C%5C6%29OD3%3A%5C%5C2-5x%3E0%5C%5Cx%3C%5Cfrac%7B2%7D%7B5%7D%5C%5Clg%282-5x%29%3D1%5C%5C2-5x%3D10%5C%5C5x%3D-8%5C%5Cx%3D-%5Cfrac%7B8%7D%7B5%7D)
0\\x>-3\\log_7(x+3)=2\\x+3=49\\x=46\\\\6)OD3:\\2-5x>0\\x<\frac{2}{5}\\lg(2-5x)=1\\2-5x=10\\5x=-8\\x=-\frac{8}{5}" alt="4)OD3:\\x+3>0\\x>-3\\log_7(x+3)=2\\x+3=49\\x=46\\\\6)OD3:\\2-5x>0\\x<\frac{2}{5}\\lg(2-5x)=1\\2-5x=10\\5x=-8\\x=-\frac{8}{5}" align="absmiddle" class="latex-formula">
![image](https://tex.z-dn.net/?f=1%29y%3Dlog_4%28x-1%29%5C%5COD3%3A%5C%5Cx-1%3E0%5C%5Cx%3E1%5C%5C%5C%5C3%29y%3Dlog_3%28x%5E2%2B2x%29%5C%5COD3%3A%5C%5Cx%5E2%2B2x%3E0%5C%5Cx%5E2%2B2x%3D0%5C%5Cx%28x%2B2%29%3D0%5C%5Cx%3D0%5C+%3Bx%3D-2)
0\\x>1\\\\3)y=log_3(x^2+2x)\\OD3:\\x^2+2x>0\\x^2+2x=0\\x(x+2)=0\\x=0\ ;x=-2" alt="1)y=log_4(x-1)\\OD3:\\x-1>0\\x>1\\\\3)y=log_3(x^2+2x)\\OD3:\\x^2+2x>0\\x^2+2x=0\\x(x+2)=0\\x=0\ ;x=-2" align="absmiddle" class="latex-formula">
/////+/////(-2)....-....(0)/////+/////->x
x=1
![image](https://tex.z-dn.net/?f=2%29y%3D%5Clog_%7B0%2C3%7D%281%2Bx%29%5C%5COD3%3A%5C%5C1%2Bx%3E0%5C%5Cx%3E-1%5C%5C%5C%5C4%29log_%7B%5Csqrt2%7D%284-x%5E2%29%5C%5COD3%3A%5C%5C4-x%5E2%3E0%5C%5C4-x%5E2%3D0%5C%5Cx%3D%5E%2B_-2)
0\\x>-1\\\\4)log_{\sqrt2}(4-x^2)\\OD3:\\4-x^2>0\\4-x^2=0\\x=^+_-2" alt="2)y=\log_{0,3}(1+x)\\OD3:\\1+x>0\\x>-1\\\\4)log_{\sqrt2}(4-x^2)\\OD3:\\4-x^2>0\\4-x^2=0\\x=^+_-2" align="absmiddle" class="latex-formula">
.........-.........(-2)/////+/////(2)......-.......->x
x=0